Estudio de la recarga inducida del acuífero del Río Chicama – Valle Chicama con fines de aprovechamiento de las Aguas Subterráneas - Espinoza Mendocilla, Maribel (2017)
The present project aims to show the possibilities of artificial recharge as an element of management of the groundwater resources of the alluvial aquifer of the Chicama River, which is a source of urban, agricultural and industrial supply in the area of influence of the Chicama River. Numerous studies carried out on the Chicama River Valley point to the need to develop a joint management of water resources, since surface and underground resources are used to meet existing demands. A study entitled "Evaluation of Superficial Water Resources in the Chicama River Basin" by the National Water Authority (ANA), which quantifies the water availability and analyzes several scenarios of potential use of the resource including water Underground and the contributions of the Chavimochic project, with the waters of the Santa River where the balance of water between supply and demand is analyzed and for the current scenario the system maintains a water deficit and therefore the areas of cultivation should be reduced , Which is not an adequate solution. The objective of this project is to analyze the hydrogeological characteristics of the river aquifer for the purpose of exploiting groundwater, such as rechargeable volumes, through the bed of the river bed and to define the effectiveness of the induced recharge of the Chicama River for the purpose of Use of groundwater, for the agricultural sector (Irrigation) and urban.